(untitled) (Journal of Economic Research & Business Administration, 2015)
Strategic Direction Policy of Russia on migration aimed at stabilizing the population and promotion sustainable socio-economic development, the implementation of its national and geopolitical interests in the period up to 2015. The effectiveness of the socio-economic transformations in Russia largely depends on ensuring that its needs in the workforce. At the same time, starting in 1992 a decline in the total population due to take place in the country of demographic processes. The population in 2026 according to stat. аgensy may change up to 125 million people. In this context, immigration is emerging as one of the strategic directions of migration policy of Russia.